Penser l’écologie politique - Fabrice Flipo (VertigO)
This paper intends to review on what the situation is regarding “political ecology”, in the framework of classical political philosophy. The most common manners to think the problem, environmental ethics and philosophy of the technique, are important but are also only the most visible part of the stake and of the way philosophers were able to get down to it ; this is what appears clearly when we examine in a more general way the reception of political ecology as an ideology within the two big currents of political philosophy which dominated the last century, the liberalism and his criticism. This perspective indicates that it is modernity, presumed to be the carrier of universalism, who is questioned, as being embedded in particularism. Material difficulties encountered by tentatives of generalization of this lifestyle are only an indicator among others, which has maybe only the peculiarity of being more visible than others. We are led to the conclusion according to which the question of the "modes of production and consumption", in the terminology of the UNO, takes root in questions which are clearly a matter of philosophic anthropology.